Targeted Polymeric Nanoparticles for Brain Delivery of High Molecular Weight Molecules in Lysosomal Storage Disorders - Salvalaio, Marika (PLoS One, 2016)
Lysosomal Storage Disorders (LSDs) are a group of metabolic syndromes, each one due to the deficit of one lysosomal enzyme. Many LSDs affect most of the organ systems and overall about 75% of the patients present neurological impairment. Enzyme Replacement Therapy, although determining some systemic clinical improvements, is ineffective on the CNS disease, due to enzymes' inability to cross the blood-brain barrier (BBB). With the aim to deliver the therapeutic enzymes across the BBB, we here assayed biodegradable and biocompatible PLGA-nanoparticles (NPs) in two murine models for LSDs, Mucopolysaccharidosis type I and II (MPS I and MPS II). PLGA-NPs were modified with a 7-aminoacid glycopeptide (g7), yet demonstrated to be able to deliver low molecular weight (MW) molecules across the BBB in rodents. We specifically investigated, for the first time, the g7-NPs ability to transfer a model drug (FITC-albumin) with a high MW, comparable to the enzymes to be delivered for LSDs brain therapy. In vivo experiments, conducted on wild-type mice and knockout mouse models for MPS I and II, also included a whole series of control injections to obtain a broad preliminary view of the procedure efficiency. Results clearly showed efficient BBB crossing of albumin in all injected mice, underlying the ability of NPs to deliver high MW molecules to the brain. These results encourage successful experiments with enzyme-loaded g7-NPs to deliver sufficient amounts of the drug to the brain district on LSDs, where exerting a corrective effect on the pathological phenotype.